Prophylactic Use of Natural Products against Developmentally Programmed Metabolic Syndrome - Ibrahim, Kasimu Ghandi; Adeshina, Kehinde Ahmad; Bello, Muhammad Bashir; Malami, Ibrahim; Abubakar, Bilyaminu; Abubakar, Murtala Bello; Imam, Mustapha Umar (Planta Medica, 2021)
Parental dietary choices and/or nutritional interventions in the offspring are critical to early life development, especially during the periods of active developmental plasticity in the offspring. Exposure to a high-fructose, high-fat diet during the fetal or neonatal period predisposes the affected individuals to the development of one or more features of metabolic syndrome, such as dyslipidemia, insulin resistance, diabetes, and associated cardiovascular diseases, later in their life. Owing to the increasing global prevalence of metabolic syndrome and multiple side effects that accompany conventional medicines, much attention is directed towards medicinal plants and phytochemicals as alternative interventions. Several studies have investigated the potential of natural agents to prevent programmed metabolic syndrome. This present review, therefore, highlights an inextricable relationship between the administration of medicinal plants or phytochemicals during the intrauterine or neonatal period, and the prevention of metabolic dysfunction in adulthood, while exploring the mechanisms by which they exert such an effect. The review also identifies plant products as a novel approach to the prevention and management of metabolic syndrome.
Keywords: developmental programing; neonatal; metabolic syndrome; phytochemicals; plant extracts